On the Importance of the Visual... and of Mentoring - HECHT, GABRIELLE (Technology and culture, 2014)
Hecht pays tribute to international scholar and technology historian Tom Hughes. He conveys that Hughes subtle brilliance, already evident in the classroom, made him magnificent mentor. Hughes found large-scale technology profoundly moving. But his admiration of Edison and other system builders didn't blind him to their foibles.